Balancing conservation priorities for grassland and forest specialist bird communities in agriculturally dominated landscapes. (January 2022) - de Zwaan, Devin R.; Alavi, Niloofar; Mitchell, Greg W.; Lapen, David R.; Duffe, Jason; Wilson, Scott
Abstract: Effective conservation planning often requires difficult decisions when at-risk species inhabit economically valuable landscapes or if the needs of multiple threatened species do not align. In the agriculture-dominated landscape of eastern Ontario and southwestern Quebec, Canada, conflicting habitat requirements exist between threatened grassland birds benefiting from certain agriculture practices, and those of a diverse woodland bird community dependent on forest recovery. Using multi-scale species distribution models with data from the North American Breeding Bird Survey (BBS), we assessed habitat suitability for 8 threatened grassland and forest specialists within this region. We also identified landscapes that jointly maximize occurrence of the 8 focal species and diversity of the full avian community. Influential habitat associations differed among species at the territory (200 m radius) and landscape level (1 km), highlighting the importance of considering multiple spatial scales. Species diversity was maximized when forest or grassland/pasture cover approached 40–50%, indicating a positive response to land cover heterogeneity. We identified species diversity hotspots near Lake Huron, as well as along the shore and southeast of the St. Lawrence River. These areas represent mosaic landscapes, balancing forest patches, wetland, grassland/pasture, and row crops such as corn, soybean, and cereals. Despite drastic landscape changes associated with agroecosystems, we demonstrate that targeted habitat protection and enhancement that prioritizes land cover diversity can maximize protection of bird communities with directly contrasting needs. We highlight multiple pathways to achieve this balance, including forest retention or separating row crops with hedgerows and wooded fence-lines, improving flexibility in conservation approaches. Highlights: Heterogeneous agroecosystems support both grassland and forest bird communities. At-risk species and high avian diversity co-occur in forest, pasture, & crop mosaics. ~48% of suitable habitat for 8 focal declining species is unprotected. Conserving priority habitat requires considering multiple spatial scales. Multiple management strategies foster similarly diverse habitats (e.g., hedgerows).